2007
DOI: 10.1007/s10493-007-9103-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological variation of bee-parasitic Tropilaelaps mites (Acari: Laelapidae): new and re-defined species

Abstract: Mites in the genus Tropilaelaps are parasites of social honeybees. Two species, Tropilaelaps clareae and T. koenigerum, have been recorded and their primary hosts are presumed to be the giant honeybees of Asia, Apis dorsata and A. laboriosa. The most common species, T. clareae, is also an economically important pest of the introduced Western honeybee (A. mellifera) throughout Asia and is considered an emerging threat to world apiculture. In the studies reported here, genetic (mtDNA CO-I and nuclear ITS1-5.8S-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 42 publications
4
91
0
Order By: Relevance
“…For example, the environmental conditions in Pakistan allow continuous rearing of brood and thus survival of Tropilaelaps (Waghchoure-Camphor and Martin 2009). According to these authors, T. clareae (likely referring to T. mercedesae based on species distribution reported by Anderson and Morgan 2007) infestations coincide with the increase in brood production (April to May). In our study, we found a negative correlation between the amount of brood and Tropilaelaps infestation, which corroborated the findings of Kavinseksan et al (2004)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the environmental conditions in Pakistan allow continuous rearing of brood and thus survival of Tropilaelaps (Waghchoure-Camphor and Martin 2009). According to these authors, T. clareae (likely referring to T. mercedesae based on species distribution reported by Anderson and Morgan 2007) infestations coincide with the increase in brood production (April to May). In our study, we found a negative correlation between the amount of brood and Tropilaelaps infestation, which corroborated the findings of Kavinseksan et al (2004)).…”
Section: Discussionmentioning
confidence: 99%
“…Although both V. destructor and T. mercedesae are observed in infesting colonies, T. mercedesae is considered to be a more serious problem of A. mellifera colonies than Varroa mites in Northern Thailand Anderson and Morgan 2007). This discrepancy in severity may be due to differences in their abilities to compete for honey bee hosts and reproduce within brood cells.…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, Tropilaelaps mites could also act as biological vectors similar to the other ectoparasitic mite V. destructor (Chen and Siede, 2007). Here we test this hypothesis by analyzing T. mercedesae (Anderson and Morgan, 2007) for the presence and replication of six honeybee viruses (KBV, SBV, CBPV, BQCV, ABPV, DWV).…”
Section: Introductionmentioning
confidence: 98%
“…The primary host of one of the better known species Tropilaelaps clareae is Apis dorsata (Laigo and Morse, 1968) but Tropilaelaps mites were able to switch to the western honeybee, Apis mellifera (Delfinado and Baker, 1961;Anderson and Morgan, 2007). Tropilaelaps clareae was first discovered on A. mellifera in the Philippines (Delfinado and Baker, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Tropilaelaps mites (Acari-Laelapidae) are ectoparasites of honeybees native to Asia (Delfinado and Baker, 1961;Laigo and Morse, 1968).The primary host of mite Tropilaelaps clareae is Apis dorsata (Laigo and Morse, 1968) but the mites also infested the western honey bee when the latter was introduced in India (Delfinado and Baker, 1961;Anderson and Morgan, 2007). Today mites (Acari) parasitizing honey bees have become a global problem.…”
Section: Introductionmentioning
confidence: 99%